Shrinkage reducing type high-strength developing admixture and cement composition
Patent Information
- Application Number
- JP2023139039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、コンクリートに用いた際に強度の増進効果が得られ、硬化後の収縮低減を図ることができる収縮低減型高強度発現混和材を提供することができる。
Smart Images

Figure 2025033358000004 
Figure 2025033358000001 
Figure 2025033358000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a shrinkage-reducing, high-strength developing admixture and a cement composition. [Background technology]
[0002] In recent years, not only in Japan but also in Asian countries such as Vietnam and China, the development of social infrastructure has progressed rapidly along with economic development. This has led to a need for the development and stable supply of civil engineering and construction materials that meet local needs.
[0003] In this environment, there is a demand for improved performance in cement concrete, and in particular, there is an increasing need for high-strength concrete in connection with the need to improve the durability and extend the lifespan of high-rise buildings and concrete structures.
[0004] Pozzolanic substances such as silica fume and fly ash are often used as admixtures for high-strength concrete. Admixtures containing pozzolanic substances are effective in increasing the strength and durability of concrete, but the mixing time required to obtain the required fluidity may be longer than that required for normal cement compositions, resulting in a longer construction time for high-strength concrete. Furthermore, if the concrete is not mixed sufficiently, the workability of the concrete may be adversely affected, for example, blockage of piping may easily occur when pumping the concrete into forms or the like.
[0005] Patent Document 1 discloses that the time required for mixing mortar can be shortened by using a cement admixture made by blending blast furnace slag powder of a specific particle size with anhydrous gypsum or with anhydrous gypsum and silica fume. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6211758 Summary of the Invention [Problem to be solved by the invention]
[0007] However, since Patent Document 1 does not provide a specific evaluation of strength, it is unclear whether the cement admixture is suitable for high-strength concrete.
[0008] In view of the above, an object of the present invention is to provide a shrinkage-reducing, high-strength admixture which, when used in concrete, has a strength-enhancing effect and can reduce shrinkage after hardening. [Means for solving the problem]
[0009] As a result of intensive research aimed at solving the above problems, the present inventors have come up with the following invention and found that the above problems can be solved.
[0010] [1] Particle size A that contains pozzolanic substances and shows the maximum volume frequency in the range of 3 to 20 μm in the volume frequency particle size distribution measured by the laser diffraction scattering method. max and particle size A max The particle size B, which shows the maximum volume frequency in the particle size range of 8 to 150 μm, is max Difference with (B max -A max ) is 130 μm or less and has a mass loss rate of 1 mass % or less after being left in an incubator at 105°C for 3 hours, and a shrinkage-reducing agent. [2] Particle size B of the high strength additive max and particle size A max The difference between max -A max ) is 30 to 100 μm. [3] The shrinkage-reducing, high-strength admixture according to [1] or [2], wherein the shrinkage-reducing agent comprises at least one selected from the group consisting of polyalkylene glycols, lower alcohol alkylene oxide adducts, glycol ether-aminoalcohol derivatives, polyethers, and alcohols. [4] The pozzolanic material comprises a first pozzolanic material which is silica fume, and a particle size B max The shrinkage reducing, high strength additive according to any one of [1] to [3], wherein the average particle size of the silica fume is attributable to the shrinkage reducing, high strength additive. [5] The pozzolanic material further comprises one or more second pozzolanic materials selected from blast furnace slag, fly ash, and metakaolin, and the second pozzolanic material has a particle size A max The shrinkage-reducing, high-strength admixture according to any one of [1] to [4], wherein the average particle size of the second pozzolanic substance is attributable to the shrinkage-reducing, high-strength admixture. [6] The shrinkage-reducing, high-strength admixture according to any one of [1] to [5], further comprising gypsum. [7] The shrinkage-reducing, high-strength admixture according to any one of [1] to [6], further comprising an expansive agent. [8] A cement composition comprising the shrinkage-reducing, high-strength admixture according to any one of [1] to [7] and cement. [9] The cement composition according to [8], further comprising reinforcing fibers. Effect of the Invention
[0011] According to the present invention, it is possible to provide a shrinkage-reducing, high-strength admixture which, when used in concrete, has a strength-enhancing effect and can reduce shrinkage after hardening. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing an example of a volume frequency particle size distribution measured by a laser diffraction scattering method in the high strength development admixture according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, one embodiment of the present invention (hereinafter, may be referred to as "this embodiment") will be described. In this specification, "parts" and "%" are based on mass unless otherwise specified.
[0014] [Shrinkage reducing, high strength additive] The shrinkage-reducing high-strength development admixture according to this embodiment includes a high-strength development admixture and a shrinkage reducing agent. The high-strength development admixture includes a pozzolanic substance, and has a particle size A that shows the maximum volume frequency in the range of 3 to 20 μm in a volume frequency particle size distribution measured by a laser diffraction scattering method. max and particle size A max The particle size B, which shows the maximum volume frequency in the particle size range of 8 to 150 μm, is max Difference with (B max -A max ) is 130 μm or less, and the mass loss rate after being left in an incubator at 105°C for 3 hours is 1% by mass or less.
[0015] The high-strength admixture described above provides a strength-enhancing effect when used in concrete, and the shrinkage-reducing agent can reduce shrinkage after hardening. Depending on the composition and ratio of the high-strength admixture and shrinkage reducing agent, it is possible to shorten the mixing time and improve the fluidity retention when used in concrete. The combination of these features can further increase the practicality of the product. Each component will be described below.
[0016] (High strength additive) The high-strength admixture according to this embodiment contains a pozzolanic substance. By containing a pozzolanic substance, a strength enhancing effect can be obtained. In addition, the admixture has a particle size A that shows the maximum volume frequency in the range of 3 to 20 μm in the volume frequency particle size distribution measured by the laser diffraction scattering method. max and particle size A max The particle size B, which shows the maximum volume frequency in the particle size range of 8 to 150 μm, is max Difference with (B max -A max (hereinafter referred to as the "maximum difference") is 130 μm or less.
[0017] To explain the above in more detail, in this embodiment, as shown in FIG. 1, for example, a particle size A showing a maximum value (for example, a peak) of the volume frequency in a volume frequency particle size distribution measured by a laser diffraction scattering method is max Particle size B is in the range of 3 to 20 μm and shows the maximum volume frequency (e.g., peak). max is particle size A max These are in the particle size range of 8 to 150 μm. max -A max ) is 130 μm or less.
[0018] The inventors have discovered that by having the above-mentioned maximum value difference, the high-strength admixture is in a state where it is easily dispersed into each particle when subjected to stirring force by mixing, and thus the mixing time can be shortened.
[0019] The maximum difference is preferably 130 μm or less, and more preferably 110 or less. max and particle size B max If the particle size A is the same, the distribution will be unimodal. max Particle size B max It is preferable that the difference between the maximum values is larger and has a clear bimodal distribution. That is, the difference between the maximum values is preferably 10 μm or more, and more preferably 40 μm or more.
[0020] In particular, from the viewpoint of improving the packing property (closest packing property) of the admixture, the maximum value difference is preferably 30 to 100 μm, and more preferably 40 to 90 μm.
[0021] In order to set the maximum difference within the desired range, for example, the time for mixing and grinding the pozzolanic substance may be adjusted. If the mixing and grinding time is long, B max becomes smaller and the maximum difference becomes smaller. Particle size A max , particle size B max The volume frequency can be measured by the method described in the Examples.
[0022] In addition, the admixture according to this embodiment has a mass loss rate of 1% by mass or less after being left in an incubator at 105° C. for 3 hours. This mass loss rate is related to the dispersion of particles, and by having the mass loss rate be 1% by mass or less, it is possible to shorten the mixing time and impart a strength enhancing effect. The mass loss rate is preferably 0.95% or less, and more preferably 0.8% or less, with the lower limit being practically about 0.2% by mass.
[0023] In order to keep the mass loss rate after leaving it in a 105°C incubator for 3 hours within the desired range, for example, granulated silica fume with a low moisture content described below may be used, or some or all of the various materials may be appropriately heated. The mass loss rate can be measured by the method described in the Examples.
[0024] The pozzolanic material preferably includes a first pozzolanic material which is silica fume, and has a particle size B max is preferably due to the average particle size of the silica fume. Particle size B max The particle size is preferably in the range of 30 to 130 μm, and more preferably in the range of 60 to 110 μm. In this specification, the average particle size refers to the volume-based average particle size (D50) measured by a laser diffraction scattering method.
[0025] The silica fume (hereinafter referred to as SF) is not particularly limited, but for example, it is SiO that is vaporized by arc heat when producing silicon alloys such as metal silicon and ferrosilicon in an electric furnace. 2 It is a spherical by-product of the solidification process of the gasoline as it cools in the flue, with a diameter of 1 μm or less. Its main component is amorphous, highly reactive SiO 2 It is.
[0026] Silica fume is classified into two types: powdered silica fume that is not granulated, and granulated silica fume that is obtained by granulating powdered silica fume. Powdered silica fume refers to silica fume described in JIS A 6207, and has a bulk density of 0.4 to 0.8 g / cm. 3 That's about it. Granulated silica fume is silica fume that is made by granulating powdered silica fume, and has a volume-based average particle size of 150 to 350 μm and a density of 2.20 to 2.30 g / cm, as measured by a laser diffraction / scattering particle size distribution analyzer. 3 , BET specific surface area is 15-25m 2 / g.
[0027] Powdered silica fume has excellent dispersibility but is prone to agglomeration during use. On the other hand, granulated silica fume does not agglomerate during use, but may have poor dispersibility. These are trade-offs, but in this embodiment, it is preferable to use at least granulated silica fume. When granulated silica fume is mixed with other materials and mixed and crushed, the agglomeration of the granulated silica fume is broken down and the maximum value difference (B max -A max ) is 130 μm, making it easier to shorten the mixing time.
[0028] The content of silica fume in the admixture is preferably 30 to 80 mass %, and more preferably 35 to 70 mass %.
[0029] It is also preferred that the pozzolanic substance further contains one or more second pozzolanic substances selected from blast furnace slag, fly ash, and metakaolin, and the particle size A max is preferably due to the average particle size of the second pozzolanic material. Particle size A max The particle size is preferably in the range of 5 to 18 μm, and more preferably in the range of 8 to 15 μm.
[0030] Blast furnace slag is molten slag discharged from a blast furnace during the steel manufacturing process, which is rapidly cooled with water or other liquids to turn it into a glassy substance, and is then crushed into powder. Granulated blast furnace slag has latent hydraulic properties and hardens when stimulated by alkali. Other materials such as molten slag made from city waste or sewage sludge, dephosphorized slag, and slowly cooled slag can also be used. The Blaine specific surface area of blast furnace slag (JIS R 5201:2015) is 2500 cm 2 / g or more is preferable, and 3000 to 4500 cm 2 / g is more preferred.
[0031] Fly ash is coal ash generated during coal combustion in coal-fired power plants, and is collected by a dust collector. In the present invention, fly ash classified into types I to IV as specified in JIS A 6201 is preferred, and type II is particularly preferred. The Blaine specific surface area of fly ash is 2500 cm 2 / g or more is preferable, and 3000 to 4500 cm 2 / g is more preferred.
[0032] Metakaolin is a mineral that has been heat-treated at around 600°C to remove the water contained within the crystal lattice in the form of OH. It is an amorphous aluminosilicate when viewed by X-rays and has pozzolanic activity. The Blaine specific surface area of metakaolin is 6000 to 18,000 cm 2 / g, and 10,000 to 15,000 cm 2 It is more preferable that the molecular weight is / g.
[0033] The content of the one or more second pozzolanic substances selected from blast furnace slag, fly ash, and metakaolin in the admixture is preferably 10 to 70 mass %, more preferably 15 to 60 mass %.
[0034] The mass ratio of the second pozzolanic substance to the first pozzolanic substance (second pozzolanic substance / first pozzolanic substance) is preferably 0.7-5, and more preferably 1-4, from the viewpoints of strength development and fluidity.
[0035] The high-strength admixture according to this embodiment preferably further contains gypsum. Gypsum is a general term for anhydrous gypsum, semi-gypsum, and dihydrate gypsum, and any of them can be used. These can also be used alone or in combination of two or more. Among them, it is preferable to select anhydrous gypsum from the viewpoint of strength development.
[0036] The particle size of the gypsum is not particularly limited, but is usually 3,000 to 8,000 cm in terms of Blaine specific surface area. 2 / g is preferred, and 4,000 to 7,000 cm 2 / g is more preferable. 2 / g or more, sufficient strength is obtained and abnormal expansion does not occur over the long term. 2 Even if it exceeds / g, no further improvement in effect can be expected. The content of gypsum in the admixture is preferably 0 to 40 mass %, and more preferably 5 to 35 mass %.
[0037] The high-strength additive according to this embodiment can be obtained by mixing and grinding the raw materials for the pozzolanic substance described above. For example, when granulated silica fume and the second pozzolanic substance are used as the raw materials, it is preferable to mix and grind them using a ball mill. Since granulated silica fume usually has a larger particle size than the second pozzolanic substance, the granulated silica fume is further pulverized by extending the grinding time using the ball mill. Therefore, the maximum value difference (B max -A max ) is 130 μm or less and can be adjusted to the desired range. In addition, the mass reduction rate can be set within a desired range by subjecting at least a portion of the mixture to a heat treatment before or after the mixing and grinding.
[0038] Furthermore, the shrinkage-reducing high-strength admixture according to the present embodiment, particularly the high-strength admixture, preferably contains an expansive material. The expansive material expands through a hydration reaction to offset the shrinkage of concrete, thereby suppressing cracks, for example. The expansive material is defined in JIS A 6202, and examples thereof include free lime, free magnesia, calcium ferrite, ettringite-based, lime-based, ettringite-lime composite, and hauyne-based materials.
[0039] The particle size of the expansive material is 2000 to 9000 cm in terms of Blaine specific surface area. 2 / g, and 3000 to 8000 cm 2 / g. 2 / g or more, the hydration reaction proceeds smoothly, and the 2 By keeping the specific surface area at 0.05 to 0.1 g / g or less, the hydration reaction does not proceed too quickly, making it easier to obtain the desired expansion. The Blaine specific surface area can be determined in accordance with JIS R 5201.
[0040] The content of the expansive material in the high-strength admixture is preferably 1.0 to 10.0 mass %, and more preferably 2.0 to 8.0 mass %, from the viewpoint of reducing durability due to DEF (delayed formation of ettringite).
[0041] (Shrinkage reducing agent) The shrinkage reducing agent lowers the surface tension of the water inside the concrete and reduces shrinkage caused by drying, for example, by suppressing cracks caused by drying. The shrinkage reducing agent may be exemplified by a surfactant, but more specifically, it is preferably at least one selected from the group consisting of polyalkylene glycol, lower alcohol alkylene oxide adduct, glycol ether-amino alcohol derivative, polyether, and alcohol. These can suppress shrinkage more effectively. Among them, polyoxyalkylene glycol is more preferable.
[0042] From the viewpoint of reducing shrinkage, the weight average molecular weight of the shrinkage reducing agent is preferably from 1000 to 30,000, and more preferably from 3,000 to 13,000. The weight average molecular weight can be determined by gel permeation chromatography (GPC) using a calibration curve prepared using standard polystyrene.
[0043] The mass ratio of the shrinkage-reducing agent to the high-strength developing admixture (shrinkage-reducing agent / high-strength developing admixture) is preferably 0.4 to 8.5, and more preferably 1.0 to 4.0, from the viewpoint of preventing air entrapment and a decrease in strength development.
[0044] In order to effectively exert its effects, the total amount of the shrinkage reducing agent and the high strength developing admixture in the shrinkage reducing high strength developing admixture is preferably 90 mass % or more, more preferably 95 mass % or more, and even more preferably 100 mass %. In addition to the shrinkage reducing agent and high strength developing admixture, additives such as water reducing agents, high performance water reducing agents, high performance water reducing agents, high performance AE water reducing agents, defoamers, hardening accelerators, rust inhibitors, antifreeze agents, and retarders may be contained.
[0045] [Cement composition] The cement composition according to this embodiment contains the shrinkage-reducing, high-strength developing admixture of the present invention and cement. Examples of cement include various types of Portland cement, such as ordinary, early strength, extra early strength, low heat, and moderate heat, various types of blended cement, and filler cement mixed with limestone powder.
[0046] The particle size of the cement composition of the present embodiment is not particularly limited since it depends on the purpose and application of the composition. Generally, the particle size is 2,500 to 8,000 cm in terms of Blaine specific surface area. 2 / g is preferable, and 3,000 to 6,000 cm 2 / g is more preferable. 2 / g or more, sufficient strength expression is obtained, and 2 / g or less can improve workability.
[0047] The cement composition may further contain an aggregate, which is not particularly limited and may be any of fine aggregates and coarse aggregates used in the manufacture of ordinary mortar or concrete. In addition, various admixtures may be contained. When the cement composition of the present embodiment contains fine aggregate, it becomes mortar, and when it contains fine aggregate and coarse aggregate, it becomes concrete.
[0048] Moreover, the cement composition of the present embodiment preferably further contains reinforcing fibers. From the viewpoints of preventing material separation of the reinforcing fibers in the composition and of the fluidity of the composition, the dimensions of the reinforcing fibers are preferably a diameter of 0.05 to 0.5 mm and a length of 5 to 30 mm, more preferably a diameter of 0.1 to 0.4 mm and a length of 8 to 25 mm, and particularly preferably a diameter of 0.1 to 0.3 mm and a length of 12 to 20 mm.
[0049] Examples of the steel material constituting the reinforcing fibers include ordinary steel, stainless steel, etc. The steel material is preferably one having alkali resistance. As the reinforcing fibers, for example, those commercially available as reinforcing fibers for fiber-reinforced concrete can be used.
[0050] The content of the reinforcing fiber is preferably 7.0 parts by mass or more and 118.0 parts by mass or less, more preferably 10.0 parts by mass or more and 16.0 parts by mass or less, and even more preferably 12.5 parts by mass or more and 15.5 parts by mass or less, relative to 100 parts by mass of cement. By having the content of the reinforcing fiber be 8.0 parts by mass or more, the effect of improving sagging can be fully exerted. In addition, by having the content of the fiber be 17.0 parts by mass or less, the bending strength can be improved without impairing the fluidity.
[0051] The cement composition of the present embodiment may be prepared by mixing the respective materials at the time of application, or may be prepared by mixing a part or all of the materials in advance. The method of mixing the respective materials and water is not particularly limited, and the respective materials may be mixed at the time of application, or may be mixed a part or all of the materials in advance. In addition, the remaining materials may be mixed after a part of the materials is mixed with water.
[0052] As the mixing device, any existing device can be used, for example, a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, a Nauta mixer, or the like. EXAMPLES
[0053] <<Experimental Example 1>> [Production of high-strength admixture] Granulated silica fume particles and at least one of ground granulated blast furnace slag, powdered fly ash, powdered metakaolin, and gypsum were loaded into a vibration pot mill (manufactured by Chuo Kakoki Co., Ltd.), ground and mixed under the conditions described below, and appropriately heated to 105°C to produce a high-strength admixture having the composition shown in the table below. In addition, the above heat treatment was not carried out for Experiment No. 6.
[0054] <Conditions for grinding and mixing process> An appropriate amount of DEG (diethylene glycol) was dropped onto the raw material filled in the vibration pot mill as a grinding aid, and the particle size A in Table 1 was obtained. max and particle size B max The mixing and grinding time was adjusted so that
[0055] <Materials used in high strength additives> · Finely ground blast furnace slag: Ground and classified blast furnace slag, average particle size 10μm Silica fume granulated particles: Commercially available product, average particle size 209 μm, BET specific surface area 18.5 m 2 / g Fly ash powder: JIS fly ash type II, density 2.35g / cm 3 , 4600cm 2 / g Metakaolin powder: Commercially available product, density 2.6g / cm 3 , Blaine specific surface area 12,000cm 2 / g Gypsum: Natural anhydrous gypsum crushed product, Blaine specific surface area 5,000 cm 2 / g
[0056] <Physical properties of high-strength admixture> Volume frequency particle size distribution measurement For each of the prepared admixtures, a laser diffraction / scattering device (product name: Laser diffraction / scattering particle size distribution measuring device LA-960, manufactured by HORIBA) was used to measure the particle size A, which shows the maximum volume frequency in the range of 3 to 20 μm. max Particle size B, which shows the maximum volume frequency in the particle size range of 8 to 150 μm max The maximum difference (B max -A max The results are shown in the table below.
[0057] - Mass loss rate measurement The mass loss rate of each of the prepared admixtures was determined after leaving them in a constant temperature dryer (product name: DVS401, manufactured by YAMATO) at 105°C for 3 hours. The results are shown in the table below.
[0058] [Shrinkage reducing agent] The following materials were prepared as shrinkage reducing agents: POA: Polyoxyalkylene glycol (Denka, weight average molecular weight 4,000 to 10,000, Denkanon Hibimaster) PEG: Polyethylene glycol (Sanyo Chemical Industries, weight average molecular weight 2,000, PEG-2000) PPG: Polypropylene glycol (Denka, weight average molecular weight 15,000 to 25,000, Denka Skeguard)
[0059] The high strength admixture and shrinkage reducing agent described above were mixed in the proportions shown in Table 1 to produce a shrinkage reducing high strength admixture, and the following evaluations were carried out on mortar using this shrinkage reducing high strength admixture. The results are shown in the table below. The materials used and the proportions for the mortar are as follows:
[0060] <Materials and mixes used in mortar> (Materials used) Mixing water: Tap water Cement: Ordinary Portland cement, commercially available, density 3.15g / cm 3 Fine aggregate: Commercially available, density 2.64g / cm 3 , coarse grain ratio 2.27 Admixtures: Commercially available products, polycarboxylic acid-based high-performance water reducers, polyoxyalkylene-based defoamers
[0061] (Composition) ·Water:205kg / m 3 Cement: 927kg / m 3 - Shrinkage reducing high strength additive in each example: 360kg / m 3 ·Fine aggregate: 905kg / m 3 High-performance water reducing agent 32.2kg / m 3 Defoamer: 6.4kg / m 3
[0062] <Mixing time> The mortar was mixed using a forced twin-axis mixer. The mixing time was recorded by recording the mixer load value every minute, and mixing was completed when it remained constant for 3 consecutive minutes. The kneading time is preferably 25 minutes or less, and more preferably 10 to 20 minutes.
[0063] <Compressive strength> The measurements were made in accordance with JSGE-G 505 "Method of testing compressive strength of mortar or cement paste using cylindrical specimens," specifically, using the following "Sample preparation method and curing method." The material age was set to 3 days after the steam curing.
[0064] (Sample preparation method and curing method) Mortar was prepared using a forced biaxial concrete mixer with a nominal capacity of 55 L, and then left in an environment of 20°C and 80% RH until the material was aged for one day. After demolding at one day, the material was heated to 85°C at a rate of 20°C / h or less, held for 24 hours, and then cooled to 20°C at a rate of 20°C / h or less.
[0065] <Method of evaluating liquidity retention> Measurements were taken in accordance with JIS R 5201 "Physical testing methods for cement (without dropping)". The flow value after 20 minutes was subtracted from the flow value immediately after mixing, and the fluidity retention effect was calculated using the following formula. Fluidity retention effect (mm) = [Flow value immediately after mixing] - [Flow value after 20 minutes] The fluidity retaining effect is preferably 30 mm or less.
[0066] <Evaluation of shrinkage reduction> In accordance with JSCE-K561-2013 5.9 Dimensional stability, the embedded strain gauge KM-100BT was used to perform continuous measurements at specified intervals using a data logger to evaluate the dimensional stability. Specifically, mortar was poured into a 10 x 10 x 40 cm steel formwork in which an embedded strain gauge (KM-100BT, Tokyo Measuring Instruments Laboratory) was installed, and the mortar was wrapped in a fluororesin sheet to prevent it from drying out. The strain on the mortar was then measured using a data logger. After the setting was completed, the formwork was loosened and the actual strain was calculated as the amount of autogenous shrinkage (×10 -6 ) was decided. The amount of self-shrinkage is -1100(×10 -6 ) or less.
[0067] [Table 1]
[0068] <<Experimental Example 2>> A shrinkage-reducing high-strength admixture was prepared in the same manner as in Experimental Example 1, except that the high-strength admixture was mixed with the expansive material shown below in the ratios shown in Table 2, and each evaluation was carried out. The results are shown in Table 2. (Expansion material) Expansive material conforming to JIS A 6202 (ettringite type or ettringite-lime composite type)
[0069] [Table 2]
[0070] <<Experimental Example 3>> A shrinkage-reducing, high-strength admixture was prepared in the same manner as in Experimental Example 1, except that reinforcing fibers were mixed in the mortar in the ratio shown in Table 3, and each evaluation was carried out. The results are shown in Table 3. The reinforcing fibers used were manufactured by Sumitomo Electric Industries, Ltd. Steel fibers, carbon fibers, aramid fibers, polyolefin fibers such as polypropylene and polyethylene, and vinyl fibers can be used as reinforcing fibers, but steel fibers were used here. Tensile strength: 2×10 -3 N / mm 2 The fibers used were 0.2 mm in diameter and 15 to 22 mm in length.
[0071] [Table 3] [Industrial Applicability]
[0072] The shrinkage-reducing, high-strength development admixture of the present invention can be suitably used in the fields of civil engineering and construction, particularly for lightweight, thin-walled concrete members that require ultra-high strength and self-leveling.
Claims
1. A particle size A that contains a pozzolanic substance and shows the maximum volume frequency in the range of 3 to 20 μm in the volume frequency particle size distribution measured by a laser diffraction scattering method. max and particle size A max The particle size B, which shows the maximum volume frequency in the particle size range of 8 to 150 μm, is max Difference with (B max -A max ) is 130 μm or less and has a mass loss rate of 1 mass % or less after being left in an incubator at 105° C. for 3 hours, and a shrinkage-reducing agent.
2. Particle size B of the high strength additive max and particle size A max The difference between (B max -A max 2. The shrinkage reducing high strength additive according to claim 1, wherein the average particle size is 30 to 100 μm.
3. The shrinkage-reducing, high-strength admixture according to claim 1, wherein the shrinkage-reducing agent comprises at least one selected from the group consisting of polyalkylene glycols, lower alcohol alkylene oxide adducts, glycol ether-aminoalcohol derivatives, polyethers, and alcohols.
4. The pozzolanic material comprises a first pozzolanic material which is silica fume, and a particle size B max The shrinkage reducing, high strength additive according to claim 1, characterized in that the average particle size of the silica fume is attributable to the shrinkage reducing, high strength additive.
5. The pozzolanic material further comprises one or more second pozzolanic materials selected from blast furnace slag, fly ash, and metakaolin, and the second pozzolanic material has a particle size A max 2. The shrinkage reducing, high strength admixture of claim 1, wherein:
6. The shrinkage reducing, high strength developing admixture according to claim 1, further comprising gypsum.
7. The shrinkage reducing, high strength additive according to claim 1, further comprising an expansive material.
8. A cement composition comprising the shrinkage reducing high strength developing admixture according to any one of claims 1 to 7 and cement.
9. The cement composition of claim 8 further comprising reinforcing fibers.
Citation Information
Patent Citations
Fluororesin composition
JP1987011758A